Analisis Pengaruh Investment Opportunity Set, Kebijakan Hutang, Profitabilitas dan Kepemilikan Manajerial Terhadap Kebijakan Dividen dan Nilai Perusahaan (Studi Pada Perusahaan yang Terdaftar Dalam Indeks Papan Utama BEI Tahun 2009 – 2016) - Nugrahandini, Yuliastanti; Pangestuti, Irene Rini Demi; Soegiono, Soegiono (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2019)
To obtain maximum returns, prospective investors must have knowledge of the fundamental aspects to be able to place their investments appropriately in the issuer's companies in the capital market. This study aims to examine whether the investment opportunity set, debt policy, profitability and managerial ownership influence the firm value by using dividend policy as an intervening variable. The sample used in this study consisted of 20 companies listed on the Main Board of IDX in the period from 2009-2016. The analysis technique used is Partial Least Square Structural Equation Modeling (PLS-SEM). The results of the study show that IOS has a negative effect on DPR and ROA has a positive effect on the DPR. While other variables did not significantly influence the DPR. The influence of IOS, ROA, and manajerial ownership significantly positive on Tobin's Q while DAR, Size and DPR had a significantly negative effect on Tobin's Q. Based on the VAF test, the DPR mediated IOS by 17.17% and mediated ROA by -4.46% or less than 20 % so that it can be concluded that there is almost no mediating role of the DPR on the relationship of IOS and ROA to the firm value.